Biological properties and potential application of hawthorn and its major functional components: A review. (March 2022) - Li, Tuoping; Fu, Siyu; Huang, Xin; Zhang, Xiushan; Cui, Yanmin; Zhang, Zuoyi; Ma, Yue; Zhang, Xuan; Yu, Qianhui; Yang, Shuning; Li, Suhong
Graphical abstract: Highlights: Hawthorn is a good source of health food and medicine. Functional characteristics of hawthorn are summarized. Phenols and flavonoids are major bioactive substances in hawthorn. Hawthorn pectin oligosaccharides are helpful to improve lipid metabolism. Polysaccharides of hawthorn can act as prebiotics. Abstract: Hawthorn ( Crataegus ) widely distribute in the world, and is known as an excellent fruit resource commonly planted in China. It has been used for food and medicine for thousands of years in China. This paper surmised the up-to-date literatures on the functional properties of flavonoids, phenols, terpenoids and polysaccharides of hawthorn. Meanwhile, the application prospects of hawthorn in functional foods are also prospected. These will be helpful for the developments of functional foods or deep-processing technologies of hawthorn.